2015
DOI: 10.2215/cjn.03830415
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Vitamin D Level and Change in Albuminuria and eGFR According to Sodium Intake

Abstract: Background and objectives Low circulating 25-hydroxyvitamin D [25(OH)D] and high sodium intake are both associated with progressive albuminuria and renal function loss in CKD. Both vitamin D and sodium intake interact with the renin-angiotensin-aldosterone system. We investigated whether plasma 25(OH)D or 1,25-dihydroxyvitamin D [1,25(OH) 2 D] is associated with developing increased albuminuria or reduced renal function and whether these associations depend on sodium intake.Design, setting, participants, & mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 45 publications
3
17
1
Order By: Relevance
“…In line with this assumption, we recently found that dietary sodium restriction potentiates the antiproteinuric and renoprotective efficacy of VDRA treatment in a rat model of proteinuric nephropathy 19 and that sodium intake modulates the inverse association between plasma vitamin D levels and the risk of developing increased albuminuria in the general population. 20 At variance, however, a post hoc analysis of the VITamin D receptor activator for Albuminuria Lowering (VITAL) trial 16 as well as an observational study in nondiabetic CKD 21 suggested that patients with albuminuria and higher baseline dietary sodium intake had a stronger antiproteinuric response to VDRA treatment than those with lower baseline sodium intake.…”
mentioning
confidence: 99%
“…In line with this assumption, we recently found that dietary sodium restriction potentiates the antiproteinuric and renoprotective efficacy of VDRA treatment in a rat model of proteinuric nephropathy 19 and that sodium intake modulates the inverse association between plasma vitamin D levels and the risk of developing increased albuminuria in the general population. 20 At variance, however, a post hoc analysis of the VITamin D receptor activator for Albuminuria Lowering (VITAL) trial 16 as well as an observational study in nondiabetic CKD 21 suggested that patients with albuminuria and higher baseline dietary sodium intake had a stronger antiproteinuric response to VDRA treatment than those with lower baseline sodium intake.…”
mentioning
confidence: 99%
“…The increased synthesis and secretion of PTH stimulates hypocalcemia, hyperphosphatemia and vitamin D defi ciency [16,17]. It is diffi cult to explain if hypocalcemia is not associated with the deposition of calcium in vessels and tissues in our patients, which is mentioned by other authors [3,4,9,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 82%
“…Coronary artery calcification has been reported in patients with CKD [82], and calcium phosphate levels have been shown to correlate with increased mortality risk in HD patients [83]. Low plasma 25(OH)D is also associated with a higher risk of developing increased albuminuria, particularly in individuals with high sodium intake [84]. Thus it is thought that correcting vitamin D levels may reduce PTH levels, correct alterations in bone turnover and calcium metabolism, and subsequently reduce mortality in the CKD population.…”
Section: Vitamin Dmentioning
confidence: 99%